2021
DOI: 10.1590/2179-8087-floram-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Community Ecology of Soil Fauna Under Periodically Flooded Forest and Anthropic Fields

Abstract: The study evaluated the ecology of soil invertebrate faunal communities in periodically flooded forest (CF) fragments and anthropic fields (AF) in the Atlantic Forest. The sampling occurred in the rainy and dry seasons using pitfall traps. We estimated the total activity, richness, diversity, and evenness as well as the activity of the taxonomic and functional groups. Total activity and richness varied as a function of seasonality. Entomobryomorpha, Poduromorpha, and Symphypleona were the most representative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The density and group number of saprophytic soil faunas are more prominent in the forests with high canopy density, moist soil, and rich litters [10]. Santos [11] found that periodically flooded forests favored groups from the saprophagous groups, while fragments and anthropic fields in the Atlantic Forest favored predator and herbivore groups, reflecting the predominant functional groups in the two different understory microhabitats. The proportions of functional groups are important biological indices to measure ecosystem function and soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…The density and group number of saprophytic soil faunas are more prominent in the forests with high canopy density, moist soil, and rich litters [10]. Santos [11] found that periodically flooded forests favored groups from the saprophagous groups, while fragments and anthropic fields in the Atlantic Forest favored predator and herbivore groups, reflecting the predominant functional groups in the two different understory microhabitats. The proportions of functional groups are important biological indices to measure ecosystem function and soil fertility.…”
Section: Introductionmentioning
confidence: 99%
“…As they are very diverse and belong to several functional groups, soil fauna can directly influence ecological functions, such as: biological control (predators, herbivores, parasites), soil decomposition and fertility (decomposers, fungivores), water regulation and soil formation (ecosystem engineers) [21][22][23][24]. Moreover, the diversity within each functional group strongly affects important ecosystem processes such as nutrient cycling, pest control, and primary productivity [25][26][27][28][29]. Springtails (Collembola) are among the most common, widespread and abundant forms of soil decomposers [30].…”
Section: Introductionmentioning
confidence: 99%